A retrospective analysis of 5-year post surgery recurrence of N0 neck and the role of methylene blue in sentinel lymph node biopsy - Mohamed Mostafa Elshamaa; Hamada mahran; Jingade Krishnojirao Dayashankara Rao; Samir Ali Elborolosy (Elsevier, 2022)
The aim of this study is to perform a retrospective analysis of the feasibility of the clinical application of SLNB using methylene blue dye (MBD) for the identification of SLN followed by frozen section biopsy to detect occult metastasis in clinically N0 necks. Hence, to know the reliability of MBD in reducing the need for extensive surgery. Methods: We retrospectively analyzed the clinic pathological data of 48 patients with early oral cancer.The SLN identiﬁcation rate (IR) was calculated in SLNB with MBD and the false-negative rate (FNR). Intra operative frozen section biopsy was done for all patients was compared with post-operative paraffin histopathology report and the prognosis of patients was analyzed. Results: Analysis of the 48 SLNB cases showed that there were significant differences in SLN successful detection rate among patients with different site (p = 0.043) and clinical presentation (p = 0.007). Similar significant results (p < 0.05) were observed with intra-operative frozen and post-operative paraffin histopathology sections. SLNs were successfully detected in 37(77.1%) patients out of 48. The intra operative frozen histopathology completely matched with the post-operative paraffin histopathology showing 39 (81.2%) negative and 09 (18.8%) positive cases. A prognostic analysis of SLN detection based on 48 patients showed that the 5-year survival rate was 100%. Conclusion: MBD has acceptable SLN identification rate and a low FNR(false negative report) in frozen sections. Stained SLNs with no SLN metastasis are associated with disease-free survival (DFS). Hence, MBD-SLN biopsy has significantly reduced the need for extensive neck dissection in N0 neck with less morbidity.